Efficacy of immediate physiotherapy after surgical release of zygomatico-coronoid ankylosis in a young child: A case report. (18th November 2022) - Dowgierd, Krzysztof; Lipowicz, Anna; Kulesa-Mrowiecka, Małgorzata; Wolański, Wojciech; Linek, Paweł; Myśliwiec, Andrzej
ABSTRACT: Background: Temporomandibular joint ankylosis (TMJ ankylosis) manifests itself as a locked jaw and reduced mouth opening. We hypothesized that the efficacy of TMJ ankylosis surgery in a child may largely depend on physiotherapeutic management. Case Description: In this case report, we present the treatment of a girl between 1 and 4 years of age, who was unable to open her jaws immediately after birth. Congenital ankylosis was diagnosed. Intervention: Two models of therapeutic management were presented, with a surgical procedure to release bone fusion adopted as a starting point. In the first model, the rehabilitation procedure started 21 days after surgery. Outcomes: Despite rehabilitation, no clinical improvement was achieved (i.e. the child was still unable to open her jaws). In the second model, rehabilitation started from the day after surgery and management according to the second model allowed for obtaining therapeutic benefits. After therapy, the girl was able to abduct the mandible to a degree allowing for improved speech and the ability to crush food. Conclusions: This clinical case shows that the efficacy of surgical procedures may depend on the type of postoperative management. It was demonstrated that physiotherapy started immediately after the procedure to release the ankylosis improved the mandible mobility outcomes for this child.